Basal-cell keratins in cervical reserve cells and a comparison to their expression in cervical intraepithelial neoplasia. - Smedts, F. (1992)
Expression of keratins 5, 14 and 17 in endocervical subcolumnar reserve cells was detected by means of immunohistochemical studies using polypeptide specific monoclonal antibodies. These particular keratins that were found among others in basal cells could also be detected to a variable extent in metaplastic and dysplastic cervical lesions. In some cases of immature squamous metaplasia all three keratin subtypes were expressed throughout the full thickness of the epithelium. In contrast, in mature squamous metaplasia a compartmentalization of these keratins was observed. Mature squamous metaplastic epithelium showed a keratin distribution pattern comparable to ectocervical squamous epithelium, with the exception of keratin 17, which was only sporadically found in the basal layer of ectocervical epithelium and was always present in the basal cells of mature squamous metaplastic epithelium. During progression of cervical intraepithelial neoplasia a clear increase in the expression of keratin 17 was observed. However, also keratins 5 and 14 were expressed. Our results demonstrate that a considerable number of premalignant lesions of the uterine cervix express the same keratins as found in the progenitor reserve cells. Lesions that lack expression of keratin 17 may form a distinct group, which are regressive in nature and do not progress into cervical cancer.